PENGARUH MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT CAHAYA BINTANG MANISE - Umiyati Tuarita; Carla Carolien Tousalwa; Fentje Salhuteru (Jurnal Administrasi Terapan, 2023)
This study aims to determine the effect of work motivation on employee performance at PT Cahaya Bintang Manise. Based on observations made by researchers at PT Cahaya Bintang Manise, problems were found in the aspect of work motivation, where giving motivation to employees at PT Cahaya Bintang Manise, namely in the form of praise and respect for the leadership, was felt to be still not optimal, where there were no awards given to employees who excel, only giving additional salary to employees who have worked for a long time at the company so that employees often feel bored with their situation resulting in them being less focused on work. Employees are also found to be often late to work, working hours are from 08.50 to 17.00 WIT but employees often come later than 09.00 WIT. The location of this research was conducted by researchers at PT Cahaya Bintang Manise which is located at Jln. Amarumatena, Suli Hamlet, Salahutu District, Central Maluku Regency. The sample is part of the number and characteristics possessed by the population Sugiono (2014). By using the census technique, the entire population was used as the research sample, so that the total sample in the study was 30 people. Data collection techniques are the methods used to collect data and other information in research on the problem that is the object of research. The data collection techniques used in this study are the interview method, the observation method and the library study method. According to the results of the regression analysis test, it can be seen that the value of a is 5.352. This value indicates that motivation (X) is zero, then employee performance (Y) will increase by 5.352. While the b value is 0.947 indicating that when there is an increase in motivation by one unit, employee performance will increase by 0.947 units. In addition, there is a positive sign (+), which means that there is a positive influence between employee motivation and performance. The effect of motivation on the performance of employees of PT. Cahaya Bintang Manise is 86.8% while the remaining 13.2% is influenced by other factors or variables not examined in this study, meaning that if motivation increases, performance will also increase.Keywords: Motivation; Performance